Efeito de eletrodos ultrassônicos na produção de hidrogênio verde. - Menezes, Christian Matheus Barbosa de (2024)
This study investigates green hydrogen production via alkaline water electrolysis, using ultrasonic fields to boost process efficiency. Green hydrogen, derived from renewable sources, serves as a vital alternative to lower greenhouse gas emissions and foster energy diversification. The effects of utilizing an ultrasonic electrode in alkaline electrolysis were examined to pinpoint enhancements in green hydrogen production efficiency. A laboratory prototype for low-cost experimental tests was constructed, powered by a set of 4 rechargeable batteries, mimicking a photovoltaic panel's effect. The research utilized a full factorial experimental design 32, testing the prototype's validity and suitable conditions for electrolysis. Conducting experiments with ultrasound (US) at a fixed frequency of 40 kHz and a specific power of 8.9 W/cm³ directly on the cathode of the galvanic cell prototype improved the electrolysis dynamics by up to 28%, including energy efficiency and hydrogen production rate.. These results suggest a potential reduction in overpotential and resistances between the electrolyte and electrodes, making the process more efficient and sustainable. The innovative approach of applying ultrasonic fields in alkaline electrolysis shows significant potential for enhancing green hydrogen production's efficiency and economic viability, contributing to renewable energy solutions and environmental sustainability.